1979
DOI: 10.1530/jrf.0.0560521
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo myometrial electrical activity in the cyclic mare

Abstract: Uterine electromyography was performed by means of chronically implanted surface electrodes in 3 Pony mares during spontaneous oestrous cycles and following luteolysis induced by a prostaglandin analogue (fluprostenol). Three distinct patterns were recognized during the oestrous cycle. (1) During oestrus well defined phases of activity with closely grouped high-amplitude spikes were separated by long periods (10-45 min) of complete inactivity. (2) During dioestrus more diffuse phases of activity with low-ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 8 publications
4
23
0
1
Order By: Relevance
“…This indicates that the smooth muscle cells of the myometrium are better electro-coupled and are working as a syncytium rather than in a nonpropagating, asynchronous fashion, as characterized by long trains of low amplitude spike activity. Taverne et al (1979b) observed that EMG activity in the cyclic mare seems to be related to the peripheral concentrations of progesterone, with little apparent correlation with the concentration of oestrogen. It would seem that this situation also exists in the pregnant mare, since EMG activity for individual mares shows similar trends throughout pregnancy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that the smooth muscle cells of the myometrium are better electro-coupled and are working as a syncytium rather than in a nonpropagating, asynchronous fashion, as characterized by long trains of low amplitude spike activity. Taverne et al (1979b) observed that EMG activity in the cyclic mare seems to be related to the peripheral concentrations of progesterone, with little apparent correlation with the concentration of oestrogen. It would seem that this situation also exists in the pregnant mare, since EMG activity for individual mares shows similar trends throughout pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Electromyographic (EMG) activity of the uterus has been recorded from pregnant sheep (Harding era/., 1982;Krishnamurtieifl/., 1982;Toutaineera/., 1983), pregnant goats (Taverne &Sheerboom, 1984), pregnant sows (Taverne et al, 1979a), pregnant cows (Zerobin & Sporri, 1972) and from the non-pregnant cyclic mare (Taverne et al, 1979b). Despite the relatively unusual nature of the hormonal environment present in the mare during pregnancy, no attempt has been made previously to describe the electrical and contractile activity of the myometrium during this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Dieses Resultat bestätigt Ergebnisse aus vorangegangenen Arbeiten, bei denen mittels Elektromyographie nach konventioneller Besamung eine Frequenzsteigerung von EMG-Spikes verzeichnet wurden (Taverne et al 1979, Jones et al 1991, Troedsson et al 1998) beziehungsweise sich mit Hilfe dynamischer Szintigramme eine Zunahme der Stärke und Frequenz von Uteruskontraktionen nach Besamung mit radioaktiv markiertem Sperma aufzeigen ließ (Katila et al 2000).…”
Section: Diskussionunclassified
“…A further complication to this subject of venereal infection is the fact that some mares are more susceptible to infection than others. The conceot of the susceotible mare stems from work pedormed by Loy, 1969 andKenney et al, 1975; and has furlher expanded the clinical interest into immunology (Asbury et al, 1982;Widders et al, 1984;Cheung et al, 1985;Hansen, 1987, Watson et al, 1987;LeBlanc et al, 1991).Interest in myometrial activity (Taverne et al, 1979;Troedsson et al, 1995) and uterine drainage (fluid accumulation) (LeBlanc, 1994a(LeBlanc, , 1994b has become a recent focus of clinical interest.…”
Section: Lntroductionmentioning
confidence: 99%